Optimization of the raw materials of biochars for the adsorption of heavy metal ions from aqueous solution - Liu, Jia (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
In this paper, the material types were preferentially selected for different kinds of heavy metals, the effect of calcination temperatures on metal adsorption was investigated, and the adsorption mechanism was explored and summarized. The results show that the pseudo-first-order kinetic was better to fit the adsorption of heavy metals. The biomass type and pyrolysis temperature had an effect on the rate at which heavy metals were absorbed. Based on their adsorbed capacity, 350 °C pyrolyzed corn stalk char, 550 °C pyrolyzed peanut shell char, 450 °C pyrolyzed peanut shell char, 450 °C pyrolyzed peanut shell char, and 500 °C pyrolyzed wheat stalk char were shown to be the best adsorbents for Cr2O72-, Cd2+, Cu2+, Zn2+ and Pb2+, respectively. The largest adsorption rate were in the order of Cr6+ (Cr2O72-, 0.5380 /min) > Pb2+ (0.2276 /min) > Cd2+ (0.1354 /min) > Cu2+ (0.1273 /min) > Zn2+ (0.1000 /min), which might be positively related to the ion radius. Meanwhile, the yield of biomass decreased from 43.9% to 29.0% with the increase of pyrolysis temperature from 350 °C to 550 °C. In addition, the specific surface area and functional groups of the biochar, as well as the ionic radius and initial concentration of heavy metals affect the adsorption rate